Online Education of Clean and Healthy Living Behavior (PHBS) in Overcoming the Spread of SARS COV-2 Virus for Gandul Cinere Village Health Cadre - Andri Pramesyanti Pramono; Lisa Safira; Retno Yulianti; Nanang Nasrullah; Novri Rahmadika (Journal of Innovation and Community Engagement, 2022)
Gandul Cinere village is located bordered by South Jakarta. Jakarta has a fairly highnumber of SARS-COV 2 positive patients. The Indonesian Government has determined thatIndonesia is entering the New Normal era in June 2020. Many people in the community donot care about health protocols in the New Normal era and consider that the Covid-19pandemic is no longer a threat. Our goals are (1) increasing PHBS knowledge andawareness of health cadres to implement PHBS and to teach the community in everyday lifein the New Normal era, and (2) decreasing incidence of Covid-19 related illness in GandulCinere Village. Therefore, a continuous understanding of health protocols is needed. PHBSis part of the health protocol that must be run in this New Normal era. Continued knowledgeprovision is required in order to prevent the transmission of Covid-19, especially in theGandul Village area, Cinere, which borders the red zone area of Covid-19. Health cadreswho are the vanguard need assistance and guidance in understanding and applying PHBS ineveryday life. The methods used were online counseling, online discussion, online mentoring,and pre-/post-test implementation. The result showed increased knowledge about Clean andHealthy Living Behavior after given counseling and discussion with the respondent.